Do transdiagnostic factors influence affective touch perception in psychiatric populations?. (February 2022) - Keizer, Anouk; Heijman, Jasmijn O; Dijkerman, H Chris
Highlights: Certain psychiatric patients show atypical perception of CT optimal touch. Childhood touch experiences may shape attachment style. Attachment style could be linked to differences in CT optimal touch perception. Touch deprivation may modulate the link between attachment and touch perception. The above relations should be further explored in psychiatric patients. Abstract : In this review, we suggest a new model that has its roots in studies with healthy individuals, but may be especially promising for understanding atypical CT optimal touch perception in certain clinical groups. We argue that social touch plays an important role in the development of a secure or insecure attachment style. Insecure attachment is common in psychiatric patients and potentially impacts their perception of CT optimal touch. This direct link between insecure attachment style and touch perception may be modulated by touch deprivation, to which individuals might be predisposed when they are insecurely attached. The links in this model need further exploration, especially in psychiatric patients, and concrete recommendations for future work are provided.